The magnetic field in the central parsec of the Galaxy. Issue 1 (16th January 2018) - Roche, P F; Lopez-Rodriguez, E; Telesco, C M; Schödel, R; Packham, C
Abstract: We present a polarization map of the warm dust emission from the minispiral in the central parsec of the Galactic Centre. The observations were made at a wavelength of 12.5 μm with CanariCam mounted on the 10.4-m Gran Telescopio Canarias. The magnetic field traced by the polarized emission from aligned dust grains is consistent with previous observations, but the increased resolution of the present data reveals considerably more information on the detailed structure of the B field and its correspondence with the filamentary emission seen in both mid-infrared continuum emission and free–free emission at cm wavelengths. The magnetic field appears to be compressed and pushed by the outflows from luminous stars in the Northern Arm, but it is not disordered by them. We identify some magnetically coherent filaments that cross the Northern Arm at a position angle of ∼45°, and which may trace orbits inclined to the primary orientation of the Northern Arm and circumnuclear disc. In the east–west bar, the magnetic fields implied by the polarization in the lower intensity regions lie predominantly along the bar at a position angle of 130°–140°. In contrast to the Northern Arm, the brighter regions of the bar tend to have lower degrees of polarization with a greater divergence in position angle compared to the local diffuse emission. It appears that the diffuse emission in the east–west bar traces the underlying field and that the bright compact sources are unrelated objects presumably projected on to the bar and with different field orientations.